Direct carotid cavernous sinus fistulae: vessel reconstruction using flow-diverting implants - Wendl, Christina M.; Bäzner, Hansjörg (Clinical neuroradiology, 2017)
PurposeRetrospective evaluation of our experience with the use of flow diverters (FD) for the endovascular treatment of direct carotid-cavernous sinus fistulae (diCCF).MethodsBetween 2011 and 2015, 14 consecutive patients with 14 diCCF were treated with FD alone or in combination with other implants in a single institution.ResultsA total of 21 sessions were performed in 14 patients. FD placement was technically successful in all cases without an adverse event. Patients were treated with FD alone (n = 5), FD and covered stents (n = 2), FD and coils (n = 7). A total of 59 FD (24 Pipeline Embolization Device, Medtronic; 35 p64 Flow Modulation Device, phenox), 291 coils, and 3 stent grafts were used. Three of 14 diCCF were completely occluded after the 1st session, a minor residual shunt was found in 7/14, and in the remaining 4/14 patients, the shunt volume was reduced significantly. The mean follow-up period encompassed 20 months. Additional treatment included transvenous coil occlusion (n = 3) and/or further FD deployment (n = 5). An asymptomatic internal carotid artery (ICA) occlusion was encountered in 2 patients, related to an interruption of antiaggregation. At the last follow-up, 10/14 patients were free from ocular symptoms (71 %), 2 had residual exophthalmos, and no patient had clinical deterioration.ConclusionThe usage of FD for the treatment of diCCF is straightforward. Injury of the cranial nerves can be avoided. In most cases, ocular symptoms improve. Several FD layers and/or an adjunctive venous coil occlusion are required. Complete occlusion of a diCCF may take weeks or months and long-term antiaggregation is required. In the future, a flexible stent graft might be a better solution.